Time integrated variation of sources of fluids and seepage dynamics archived in authigenic carbonates from Gulf of Mexico Gas Hydrate Seafloor Observatory - Feng, D; Birgel, D; Peckmann, J; Roberts, H H; Joye, S B; Sassen, R; Liu, X-L; Hinrichs, K -U; Chen, D (Chemical Geology, 2014)
Authigenic carbonate rocks recovered from the Gulf of Mexico Gas Hydrate Seafloor Observatory in Mississippi Canyon block 118 (MC118) at approximately 900 m water depth were studied using mineralogical, bulk geochemical, and lipid biomarker analyses. Carbonate rocks occurred as fractured blocks and nodular masses incorporated in carbonate breccias. The carbonates were comprised mainly of high-Mg-calcite and aragonite. The stable carbon isotope composition ($δ$13C) of authigenic carbonate varied from − 29.8‰ to − 18.1‰ vs. V-PDB, suggesting a complex mixture of various carbon sources, including dissolved marine inorganic carbon (DIC), oil, as well as methane. Oxygen isotopes ($δ$18O) varied from + 3.4‰ to + 5.8‰. The observed 18O-enrichment in relation to calculated equilibrium values in the carbonates probably reflects decomposition of gas hydrates. The most abundant lipid biomarkers in the carbonates were isoprenoidal glycerol dibiphytanyl glycerol tetraethers (GDGTs), predominated by GDGT-2 and GDGT-3, which are typically indicators of anaerobic methane oxidizing archaea (ANMEs). Mono- and bicyclic biphytanes (derived after ether cleavage of GDGT-2 and GDGT-3) showed strong 13C-depletion, which is characteristic for ANMEs. Interestingly, large differences between the $δ$13C values of the archaeal diether archaeol and acyclic biphytane on the one hand and monocyclic biphytane on the other hand suggest the presence of archaea other than ANMEs. Archaeol and GDGT-0 (containing two acyclic biphytane moieties) are commonly assigned to various methanogenic archaea. Where methane seepage activity is intermediate or low within acoustic wipeout zones at the MC118 gas hydrate site nowadays, microbial communities must have coped with changing conditions as well as longer-term fluctuations in oil and gas seepage or the temporary cessation of hydrocarbon flux in the past. The change from methane seepage to oil seepage or vice versa in addition to flux variability apparently favors the establishment of complex prokaryotic communities dominated by archaea. In addition to anaerobic oxidation of methane, local production of methane is apparently prominent at the study site based on the occurrence of biomarkers of methanogens in the authigenic carbonate. This finding adds to the ongoing multidisciplinary effort to better constrain the environment at the MC118 observatory site and to determine the locally dominant biogeochemical processes.
Keywords: HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)